Development of PI controller for battery charger using power factor correction rectifier / Mohamad Fazrino Mohd Idris - Mohd Idris, Mohamad Fazrino (2013)
This paper illustrates simulation evaluations of a PI Controller of battery Charger employing Power Factor Correction (PFC) rectifier using MATLAB Simulink simulation packages and will be compared with hardware prototype. The proposed system will use single phase incorporated with proportional-integral control technique to gives appropriate compensation to resolve problems caused by the load such as current displacement, current harmonics and to improves PF. The output current of single-phase rectifier will be used as reference current for PI Controller. The results obtain will compared and improves with more establish topology and techniques.